2021
DOI: 10.1021/acsphotonics.1c01364
|View full text |Cite
|
Sign up to set email alerts
|

All-Optical Switching of Silicon Nanobeam Cavities with an Ultra-compact Heater Utilizing the Photothermal Effect

Abstract: Strong light absorption by a metal-on-silicon hybrid waveguide structure can realize efficient photothermal conversion at a microscale. Based on the photothermal effect, an all-optical switch with an ultra-high tuning efficiency is experimentally demonstrated based on a suspended photonic crystal nanobeam cavity integrated with an ultra-compact metal optical heater. The measurement results exhibit a high photothermal efficiency of 15.52 nm/mW. The rising and falling times of all-optical switching are ∼6.8 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We believe that investigating the photothermal effects that are convenient for suppressing the Brownian fluctuations of the microlever [29,52] and quantum ground state cooling of a mechanical resonator [31] can facilitate the development of cavity-based experiments that rely on high sensitivity. Recent advances in the development of a photothermal effects-based all-optical switch with ultrahigh tuning efficiency [57] may result in a functionally integrated component that can be employed in a broad range of efficient all-optical control applications. Moreover, despite the fact that photothermal forces are dissipative forces, it has been shown that a strong coupling strength can improve optomechanical entanglement [58].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that investigating the photothermal effects that are convenient for suppressing the Brownian fluctuations of the microlever [29,52] and quantum ground state cooling of a mechanical resonator [31] can facilitate the development of cavity-based experiments that rely on high sensitivity. Recent advances in the development of a photothermal effects-based all-optical switch with ultrahigh tuning efficiency [57] may result in a functionally integrated component that can be employed in a broad range of efficient all-optical control applications. Moreover, despite the fact that photothermal forces are dissipative forces, it has been shown that a strong coupling strength can improve optomechanical entanglement [58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a silica cladding layer between the silicon waveguides and the metallic micro-heaters is usually needed to avoid light absorption caused by the metal, which also limits the heating efficiency. As a result, numerous strategies to enhance heating efficiency have been proposed, including transparent graphene nano-heaters 3 , suspended waveguide structures 4 , and photothermal effects 5 . Among these schemes, all-optically TO tunable devices as an alternative have attracted increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…O PTICAL switch, as the key component, has been widely researched and applied on reconfigurable optical add-drop multiplexing (ROADM) and optical cross connection (OXC) systems [1]- [3]. Several optical switches have been demonstrated on different platforms, including silicon-on-insulator (SOI) [4]- [8], silicon nitride (SiN) [9]- [11], silica-based planar lightwave circuits (PLCs) [12]- [16] and polymer-based PLCs [17]- [20]. The low loss waveguide and high coupling efficiency contribute silica-based switch is commercially available and can provide up to 32 ports switching with a fiber-to-fiber loss of 6.6 dB [21].…”
Section: Introductionmentioning
confidence: 99%